Source Contribution of Firecrackers Burst vs. Long-Range Transport of Biomass Burning Emissions Over an Urban Background - Rajput, Prashant; Singh, Amit Kumar; Biswas, Kaniska; Qadri, Adnan Mateen; Gupta, Tarun (Frontiers in Sustainable Cities, 2021)
This study reports on the high-resolution data set of ground-level O3, surface-bound polycyclic aromatic hydrocarbons (SB-PAHs), and particle’s number concentrations (from 10‒1000 nm, referred to as condensation nucleus concentration: CNC) during a Diwali festival campaign (conducted from 08th to 16th Nov. 2015) at Kanpur location. In this study, we have made an attempt to assess the change in atmospheric composition and chemistry (based on SB-PAHs, O3, and CNC) during Diwali festival (11th Nov.) and compared the results with pre-Diwali (08th to 10th Nov.) and post-Diwali (12th to 16th Nov.) scenarios. The wind pattern and cluster analysis have revealed a quite similar feature that from 10‒16th of November the prevailed winds were north-westerly (NW). It is noteworthy that NW-winds during post-monsoon season (Oct‒Nov) favours the long-range transport of biomass burning emissions (LRT-BB) from its source region in upwind Indo-Gangetic Plain (IGP). The influence of LRT-BB emissions at the receptor site during Diwali and post-Diwali period was reflected by the substantial increase in average concentrations of O3 and CNC (difference has been ascertained from a two-tailed t-test). The Lenshchow-type analysis suggests that the LRT-BB emissions increased the concentrations of CNC and O3 to 86% and 31%, respectively over the urban background level. On the other hand, the firecrackers (FC) burst on Diwali was found to increase the concentrations of CNC and O3 to 54% and 12% (over the urban background), respectively. However, the SB-PAHs concentrations were found to be decreased to 2% and 6%, respectively during the LRT-BB emissions and FC burst activity. Based on the observations pertaining to the decrease in SB-PAHs concentrations from the Lenschow-type analysis and anti-correlation between SB-PAHs and O3 the chemical reactivity and loss of SB-PAHs has been inferred in this study.